Aksjologiczno-moralne zobojętnienie jako wyzwanie współczesności - Zabielski, Józef (Społeczeństwo, 2022)
The presented characteristic of the phenomenon of axiological and moral indifference and its outcome shows the deformity of human nature and morality. Human morality can be improved by proper consideration of the natural law and right to live in accordance with human nature. By providing humans with personality, God gave them the chance to have a decent life.